EVALUATING THE ELECTRONIC GOVERNMENT IMPLEMENTATION IN THE KURDISTAN REGION OF IRAQ FROM CITIZENS’ PERSPECTIVE - Yahia , Hazha; Miran , Ara (Humanities Journal of University of Zakho, 2022)
The rapid development of technology affected how people think, interact, and do business and led governments in many countries to change how they interact with their citizens. The development of information and communication technologies increased citizens’ need for more transparent governments with less bureaucracy and routines. In addition, citizens need to be the center of the government decisions that affect their lives. Since 2007, the Kurdistan regional government announced strong e-government based on technology, changing traditional governance to e-governance and e-services, reducing bureaucracy, and tackling corruption. Although the e-government in KRI is still at the beginning, this quantitative article aims to assess the advancement of e-government in the Kurdistan regional government by utilizing one of the maturity models, the Layne and Lee model, and determining the e-government process’s maturity level. For the first and second levels of evaluation, this research will analyze the citizen’s perspectives and opinions through analyzing the data obtained from a questionnaire prepared for this purpose. The evaluation analysis results show that the process is prolonged, and most people are not familiar with the e-services and do not expect more progress in this area shortly.